Constraining the Solomon Sea as a source of Al and Mn to the Equatorial Undercurrent. (August 2021) - Michael, Susanna; Resing, Joseph; Lacan, Francois; Buck, Nathaniel; Pradoux, Catherine; Jeandel, Catherine
Abstract: Total dissolvable and dissolved aluminum (TDAl, DAl) and manganese (TDMn, DMn) concentrations were measured at 12 stations in and around the Solomon Sea in 2012 as part of the GEOTRACES GP-12 cruise. These data were used to determine the potential for the Solomon Sea to act as a source of Al and Mn to the Equatorial Undercurrent (EUC). From a net budget perspective, waters entering the Solomon Sea at the time of the cruise were already enriched in Al and Mn, and as that water transited through the Solomon Sea, further net enrichments were small compared to overall concentrations of these metals. Despite this overall balance, on a local scale, we observed enrichment of Al and Mn at stations located near coastlines, most likely caused by sediment scouring by strong currents. Calculated fluxes of DAl, and TDAl out of the Solomon Sea relative to the EUC are large enough to account for about three quarters of their respective budgets within the EUC, while the DMn and TDMn fluxes exiting the Solomon Sea can only account for about half of their respective budgets in the EUC. These fluxes are subject to high temporal variability and to uncertainty of the relative contributions of Northern and Southern Hemisphere water mass to the EUC. Highlights: Al and Mn are not significantly enriched during transit through the Solomon Sea. Fluxes of Al and Mn into and out of the Solomon Sea are almost equal. Al and Mn are elevated near continental shelves and margins in the Solomon Sea. Local enrichments must be balanced by boundary exchange and scavenging processes. Water exiting the Solomon Sea accounts for ca. half the flux of Al and Mn in the EUC.